Climate change adaptation and mitigation through land use decision making in Malaysia - Syed Abdul Kader, Sharifah Zubaidah; Mustafa, Maizatun; Sufian, Azlinor (2012)
Climate change in Malaysia has seen the rise in sea levels, the occurrence of floods and landslides, coastal and land erosion, drought, forest fires and haze. Malaysia signed the United Nations Framework Convention on Climate Change („UNFCC‟) in 1993 and ratified it in 1994. Malaysia also ratified the Kyoto Protocol in 2004. The UNFCC prescribes two main strategies to address climate change namely, adaptation and mitigation. Adaptation refers to adjustment in natural or human systems in response to actual or expected climatic stimuli or their effects, which moderates harm or exploits beneficial opportunities. Mitigation, on the other hand, refers to actions taken to reduce greenhouse gas emissions (one of the main causes of global warming) and to enhance carbon sinks to lessen the impacts of climate change. Land use decision making is the process of arriving at decisions by approving authorities in respect of approving or rejecting applications relating to land, planning, building and the environment. Approving authorities, when treating such applications, are primarily bound by the respective laws governing such applications as well as policies and directives of any federal supervisory body and departmental guidelines. Land use decision making is a potential tool that could be tapped by the Malaysian government to adapt to and mitigate the effects of climate change. This paper aims to examine this potential from a macro angle through qualitative means by firstly, identifying the policies and agendas for action that are already in place and secondly, identifying the main approving authorities within the legal and institutional framework in the land use decision making process that could make a difference by incorporating such policies and agendas for action. The paper concludes that such framework already exists at federal level but needs to be properly cascaded and implemented at the state and local government levels to see effective adaptation and mitigation. It offers suggestions on how this can be done through legal and institutional reform.